Pengaruh Pengetahuan Investasi, Modal Minimal, Motivasi Investasi, dan Kemajuan Teknologi terhadap Minat Masyarakat Kota Samarinda Berinvestasi di Pasar Modal - Permana, Diyah; Ramadhani, Fadila Putri (Jurnal EKSIS, 2024)
This research aims to: (1) determine the influence of investment knowledge, (2) determine the influence of minimal capital, (3) determine the influence of investment motivation, (4) determine the influence of tecnological advancements, and (5) determine the influence of investment knowledge, minimal capital, investment motivation, and technological advancements on the interest of the samarinda city community in investing in the capital market. Data collection techniques used questionnaires distributed both online and offline to 384 residents of Samarinda city within the productive age category (18-64 years) who have not yet invested. Data analysis techniques involved multiple linier regression analysis processed using SPSS version 23. The result showed that partially, the variabels of investment knowledge, minimal capital, investment motivation, and technological advancements all had a positive nd significant influence on the interest of the Samarinda city community in investing in the capital market. Simultaneously, investment knowledge, minimal capital, investment motivation, and technological advancements positively and significantly influenced the interest of the Samarinda city community in investing in the capital market.